The Sustainability in the Industry of Green Apparel: Are We Ready? - Shafie, Sharifah; Kamis, Arasinah (International Journal of Psychosocial Rehabilitation, 2019)
The fashion industry is the biggest contributor to social and environmental problems starting with the manufacturing process to the consumers’ disposal behavior. Generally, in Malaysia people are aware of environmental issues but the level of practices and attitudes towards environmental protection are still below expectation. The purpose of this study is to examine the factors that hinder the sustainable design and production and environmentally friendly clothing. The qualitative study design was selected using in-depth interview techniques. There were six persons comprising of clothing industry experts and lecturers from the fashion field were selected as respondents in this study. The findings indicated that factors that interfere with the design and production of sustainable clothing are materials, prices, awareness and individual responsibility. These factors were seen to impact on consumer purchasing, fashion decisions and consumer clothing production. Moreover, the implications of this study may be recommended to all stakeholders in the field of apparel in order to apply sustainability in apparel and sustainability in education to the younger generation. Therefore, the next generation need to realize the importance and responsibility of caring and protecting the environment, especially in the field of fashion, in order to adopt sustainable consumer behaviour and producing sustainable manufacturers.